Resources of Psychological Pressures and Adaptation Strategies among Teenagers - Khalid Jabbar, Mushtaq (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the current research is to identify the sources of psychological stress among displaced adolescents in Iraq and the coping strategies they use. The research sample consisted of (382) adolescent students in secondary schools. The results of the research showed that the most prominent sources of psychological stress among the displaced adolescents in Iraq from their point of view were the sources of social pressure, followed by sources of family pressure, then sources of economic pressure and sources of internal stress came, sources of emotional stress ranked fourth, and sources of behavioral pressure ranked sixth, The sources of academic stress came in the seventh rank, and the eighth and last ranks were the sources of physical pressure. And that the most prominent adaptation strategies used by displaced adolescents in Iraq were the strategy of cognitive reconstruction and the strategy of self-blame, followed by the strategy of social support and the strategy of genealogy and avoidance came fourth, and came the fifth ranked the strategy of problem solving and active dealing, and ranked sixth the strategy of relaxation and entertainment, and the seventh came the strategy Religiosity ranked eighth and last emotional emptying strategy.